Dural venous sinus angioplasty and stenting for the treatment of idiopathic intracranial hypertension. (5th December 2011) - Fields, Jeremy D; Javedani, Parisa P; Falardeau, Julie; Nesbit, Gary M; Dogan, Aclan; Helseth, Erek K; Liu, Kenneth C; Barnwell, Stanley L; Petersen, Bryan D
Abstract : Background: Lumboperitoneal shunt (LPS), ventriculoperitoneal shunt (VPS) and optic nerve sheath fenestration (ONSF) are accepted surgical therapies for medically refractory idiopathic intracranial hypertension (IIH). In the subset of patients with IIH and venous sinus stenosis, dural venous sinus stenting has emerged as an alternative surgical approach. Methods: All cases of dural stents for IIH at our institution were retrospectively reviewed. Eligibility criteria included medically refractory IIH with documented papilledema and dural venous sinus stenosis of the dominant venous outflow system (gradient ≥10 mm Hg). Results: Fifteen cases (all women) of mean age 34 years were identified. All had failed medical therapy and six had failed surgical intervention. Technical success was achieved in all patients without major periprocedural complications. The mean preprocedural gradient across the venous stenosis was reduced from 24 mm Hg before the procedure to 4 mm Hg after the procedure. Headache resolved or improved in 10 patients. Papilledema resolved in all patients and visual acuity stabilized or improved in 14 patients. There were no instances of restenosis among the 14 patients with follow-up imaging. Conclusion: In this small case series, dural sinus stenting for IIH was performed safely with a high degree of technical success and with excellent clinical outcomes. These results suggest that angioplasty and stenting for the treatment of medically refractory IIH in patients with dural sinus stenosis warrants further investigation as an alternative to LPS, VPS and ONSF.